Different particle size silicas from water glass. - Martines, MAU; Davolos, Marian Rosaly [UNESP]; Jafelicci Júnior, Miguel [UNESP] (Soc Brasileira Quimica, 1996)
Non-crystalline silica was obtained with different particle sizes. Samples were prepared from soluble sodium silicate (water glass) and sulfuric acid solutions. Dialysis was performed for sodium sulfate elimination. Products were dried in a microwave oven, milled and characterized by X-ray powder diffraction, infrared spectrum and sedigraphic analysis. Products milled for more than 120 minutes showed uniform particle size distribution with average silica particle size of 4.5 mu m.
Keywords: silica; soluble sodium silicate; particle size